Acetaminophen Use and Risk of Myocardial Infarction and Stroke in a Hypertensive Cohort. Issue 5 (May 2015) - Fulton, Rachael L.; Walters, Matthew R.; Morton, Ross; Touyz, Rhian M.; Dominiczak, Anna F.; Morrison, David S.; Padmanabhan, Sandosh; Meredith, Peter A.; McInnes, Gordon T.; Dawson, Jesse
<x xml:space="preserve">Abstract</x> Recent data suggest that self-reported acetaminophen use is associated with increased risk of cardiovascular events and that acetaminophen causes a modest blood pressure rise. There are no randomized trials or studies using verified prescription data of this relationship. We aimed to assess the relationship between verified acetaminophen prescription data and risk of myocardial infarction or stroke in patients with hypertension. We performed a retrospective data analysis using information contained within the UK Clinical Research Practice Datalink. Multivariable Cox proportional hazard models were used to estimate hazard ratios for myocardial infarction (primary end point), stroke, and any cardiovascular event (secondary end points) associated with acetaminophen use during a 10-year period. Acetaminophen exposure was a time-dependent variable. A propensity-matched design was also used to reduce potential for confounding. We included 24 496 hypertensive individuals aged ≥65 years. Of these, 10 878 were acetaminophen-exposed and 13 618 were not. There was no relationship between risk of myocardial infarction, stroke, or any cardiovascular event and acetaminophen exposure on adjusted analysis (hazard ratio, 0.98; 95% confidence interval, 0.76–1.27; hazard ratio, 1.09; 95% confidence interval, 0.86–1.38; and hazard ratio, 1.17; 95% confidence interval, 0.99–1.37; respectively). Results in the propensity-matched sample (n=4000 per group) and when men and women were analyzed separately were similar. High-frequency users (defined as receiving a prescription for >75% of months) were also not at increased risk. After allowance for potentially confounding variables, the use of acetaminophen was not associated with an increased risk of myocardial infarction or stroke in a large cohort of hypertensive patients.